Teachers' readiness in implementing school-based assessment / Salbi Abu Bakar - Abu Bakar, Salbi (2012)
The main purpose of this study was to determine teachers' readiness in implementing School-Based Assessment in primary schools. The objectives of the study are firstly to find out whether the teachers have knowledge about the School-Based Assessment; secondly, to find out whether the teachers are given adequate knowledge to implement the assessment; thirdly, the study was aimed to determine whether the teachers are ready to implement the new form of assessment; fourthly, the study aims to identify the problems faced by the teachers in implementing the School-Based Assessment; and finally, the study intended to solicit the teachers' recommendation in implementing the School-Based Assessment. The respondents consist of 98 Year One teachers from 15 primary schools in Kuching, Sarawak. A questionnaire consisting of 5 sections according to the research objectives was specially designed and developed for the purpose of this study. The findings were presented in percentages and illustrated using tables. The findings of the study show that most of the teachers have knowledge of School-Based Assessment and they were given adequate training in order to implement the new assessment system. In addition, the respondents gave positive response and indicated that they are ready to implement the School-Based Assessment. However, there were problems and challenges faced by these teachers in implementing the School-Based Assessment. Thus, recommendations are put forward to the Ministry of Education Malaysia particularly the Malaysian Examination Syndicate that may enable the teachers to implement School-Based Assessment confidently and effectively.